2003
DOI: 10.1046/j.1523-1755.2003.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential importance of glomerular citrate synthase activity in remnant nephropathy

Abstract: Citrate synthase activity is elevated in remnant glomeruli, and experimental models characterized by reduced glomerular citrate synthase activity (Wistar-Furth rats, adrenalectomized Sprague-Dawley rats) are protected from remnant nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(7 reference statements)
1
7
0
Order By: Relevance
“…Although mean arterial BP was 20 mmHg lower in Wistar-Furth rats than Wistar rats with 5/6 nephrectomy, albuminuria remained more than 10-fold higher in Wistar rats with 5/6 nephrectomy that had BP controlled to an equal level by a hydralazine-reserpinehydrochlorothiazide treatment regimen. Isolated glomeruli from Wistar-Furth rats, unlike Wistar rats, showed no increase in citrate synthase in response to direct application of aldosterone [6]. These findings further support the hypothesis that aldosterone itself has a role in mediating progressive renal disease through a mechanism that does not involve alterations in BP.…”
Section: Alterations In Aldosterone Responsivenesssupporting
confidence: 72%
See 1 more Smart Citation
“…Although mean arterial BP was 20 mmHg lower in Wistar-Furth rats than Wistar rats with 5/6 nephrectomy, albuminuria remained more than 10-fold higher in Wistar rats with 5/6 nephrectomy that had BP controlled to an equal level by a hydralazine-reserpinehydrochlorothiazide treatment regimen. Isolated glomeruli from Wistar-Furth rats, unlike Wistar rats, showed no increase in citrate synthase in response to direct application of aldosterone [6]. These findings further support the hypothesis that aldosterone itself has a role in mediating progressive renal disease through a mechanism that does not involve alterations in BP.…”
Section: Alterations In Aldosterone Responsivenesssupporting
confidence: 72%
“…It is here that aldosterone governs the vectorial transport of water and electrolytes by acting as the principal ligand for the MR. Immunohistochemical labeling of isolated rat preglomerular vasculature [5] and glomeruli [4] for MR has also been documented. Studies by Ullian and coworkers have shown that aldosterone can directly stimulate citrate synthase in isolated glomeruli from Wistar rats [6]. Aldosterone has long been known to stimulate citrate synthase, a Krebs cycle enzyme, in the kidney and the heart [7] and by doing so may enhance mitochondrial oxidative phosphorylation and oxygen free radical generation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental models with reduced glomerular citrate synthase activity are protected from remnant nephropathy [36]. It can be hypothesized that changes in intracellular citrate concentration may also have direct actions.…”
Section: Citrate Effectsmentioning
confidence: 99%
“…In the reduced renal mass model, animals develop remnant nephropathy characterized by augmented citrate synthase activity, plasma aldosterone levels and activity, and development of glomerular hypertrophy, adrenal hypertrophy, arterial hypertension, proteinuria, and structural renal injury in most animals. These effects, including plasma aldosterone levels, are decreased when the animals undergo subtotal nephrectomy with adrenalectomy [35][36][37][38][39]. Similarly, animal models that either lack aldosterone (adrenalectomized Sprague-Dawley rats) or are resistant to aldosterone actions (Wistar-Furth rats) are characterized by resistance to remnant nephropathy [36,[38][39][40][41].…”
Section: Aldosterone Synthesis and Receptorsmentioning
confidence: 99%
“…These effects, including plasma aldosterone levels, are decreased when the animals undergo subtotal nephrectomy with adrenalectomy [35][36][37][38][39]. Similarly, animal models that either lack aldosterone (adrenalectomized Sprague-Dawley rats) or are resistant to aldosterone actions (Wistar-Furth rats) are characterized by resistance to remnant nephropathy [36,[38][39][40][41]. If aldosterone is reinstituted via an infusion, it markedly increases the blood pressure in adrenalectomized spontaneously hypertensive rats [42], induces lesions of malignant nephrosclerosis in the deoxycorticosterone acetate-salt hypertensive rat model [43], and restores proteinuria and glomerulosclerosis in remnant rats treated with losartan and enalapril to an extent similar to that seen in untreated remnant rats [44].…”
Section: Aldosterone Synthesis and Receptorsmentioning
confidence: 99%